Prediction of indexes of airport operation wich meteorological condition taken into account - Халімон, Н. Ф. (Proceedings of National Aviation University, 2000)
Prognostical were airport operation indexes wich meteorologacal conditions taken into account. Determaned were coefficients of airport functioning. Presented are the results of modulation of airport operation in difficult meteorological conditions as a complex of mass maintenance